What is the economic value of literacy and numeracy? - M. Gemma Cherry; Anna Vignoles (IZA World of Labor, 2020)
Even in OECD countries, where an increasing proportion of the workforce has a university degree, the value of basic skills in literacy and numeracy remains high. Indeed, in some countries the return for such skills, in the form of higher wages, is sufficiently large to suggest that they are in high demand and that there is a relative scarcity. Policymakers need robust evidence in order to devise interventions that genuinely improve basic skills, not just of new school leavers entering the market, but also of the existing workforce. This would lead to significant improvements in the population that achieves a minimum level of literacy and numeracy.
Keywords: I2; I24; I26; J24; 330; basic skills; literacy; numeracy; wages; education policy